Cultural Conceptualisations in Visual Artifacts of Vietnamese EFL Materials: A Cultural Linguistics Analysis of an Academic English Textbook (The International Journal of Language Studies (ISSN : 3078 - 2244), 2026)
This study investigates the role of visual artifacts in an academic English listening and speaking textbook commonly used in Vietnamese EFL contexts, employing the framework of cultural linguistics as proposed by Sharifian (2017). Drawing on the concepts of cultural schemas and cultural conceptualisations, the analysis examines how visuals, such as representations of urbanisation in architecture-themed units or environmental degradation in ecology-focused sections, embody Western-centric ideologies, often marginalising Vietnamese cultural categories like collectivist harmony or ecological balance, rooted in Confucian and agrarian traditions. Utilising multimodal discourse analysis (Kress & van Leeuwen, 2006) on selected visuals and qualitative surveys with 37 Vietnamese university students, the research identifies intercultural mismatches that hinder metacultural competence, potentially leading to pragmatic failures in cross-cultural communication. Findings suggest that supplementing these visuals with localised elements, such as depictions of Vietnamese communal festivals or rural landscapes, can enhance learners’ ability to negotiate distributed cognition across linguistic boundaries. Implications for ELT materials design underscore the need for glocalised approaches in non-native speaker contexts, aligning with recent scholarship on visual semiotics in Asian EFL textbooks (e.g., Chen, 2010).
Keywords: Cultural conceptualisations; Cultural linguistics; Visual artifacts; Metacultural competence.